Scenario of Library Services in the Electronic Information ERA: The Impact of the Internet Revolution on Library Services (Journal of Advances and Scholarly Researches in Allied Education, 2019)
A library's collection growth is a consistent process and does respond to the requirements as well as objectives of the users of its. It provides not simply the policy of compilation growth itself but additionally the methods of selection, evaluation as well as acquisition. Today the web has revolutionized the standard library pursuits viz document acquisition, technical processing, circulation, reference service, resource sharing, document delivery, etc. In the contemporary world of info explosion, the internet is now needed for the libraries. Even though the Internet revolution is actually leading to big changes for librarians all over the planet, it's still in its building phase in the Indian libraries. Although, you will find a rather few technocrats who've simply jumped on the bandwagon to generate almost everything computerized and networked still a lot of librarians haven't kept pace with the technology.